Multisensoric Stimulation to Resolve Language Disorders on Children with Specific Language Impairment - Heriwanty Heriwanty; Anang Santoso; Mudjianto Mudjianto; Syamsudin Syamsudin (Universitas Negeri Malang, 2015)
Stimulasi Multisensorik untuk Mengatasi Gangguan Berbahasa pada Anak yang Mengalami Specific Language Impairment Abstract: This study is aimed (1) to uncover the causes of language disorders in children who have SLI, (2) deficits in the language of children with SLI, (3) illustrates the carrying on multi-sensory in-tervention stimulation, and (4) describe the development of language skills children who have SLI after undergoing multi-sensory stimulation intervention. Subjects were girls aged 6 years and 9 months. The Data were collected by participatory observation, interview and document study. The results of the study are (1) the language environment that is less stimulus and history of language disorders in family are affecting  language skills of children who have SLI, (2) a deficit of language of children with specific language impairment is very complex, (3) the implementation of interventions in the form of multi-sensory stimulation involve sensory modality audio-visual-kinesthetic-tactile simultaneously, and (4) implementation multi-sensory stimulation can improve language skills and non-language abilities of children with SLI. Key Words: multi-sensory stimulation, language disorders, specific language impairment Abstrak: Penelitian ini bertujuan (1) mengungkap penyebab gangguan berbahasa pada anak yang mengalami SLI, (2) defisit-defisit kebahasaan pada anak yang mengalami SLI,(3) menggambarkan pe-laksanaan intervensi stimulasi multisensorik, dan (4) menggambarkan perkembangan kemampuan berbahasa anak yang mengalami SLI setelah menjalani intervensi stimulasi multisensorik. Subjek pe-nelitian adalah anak perempuan berusia 6 tahun 9 bulan. Data dikumpulkan dengan observasi partisipatori, wawancara mendalam, dan studi dokumen. Hasil penelitian adalah (1) lingkungan bahasa yang kurang stimulus dan riwayat gangguan berbahasa keluarga sangat mempengaruhi kemampuan berba-hasa anak yang mengalami SLI, (2) defisit kebahasaan pada anak yang mengalami specific language impairment sangat kompleks, (3) pelaksanaan intervensi dalam bentuk stimulasi multisensorik melibat-kan modalitas sensorik audio-visual-kinestetik-taktil secara simultan, dan (4) penerapan stimulasi multisensorik dapat meningkatkan kemampuan berbahasa sekaligus kemampuan nonkebahasaan pada anak yang mengalami SLI. Kata kunci: stimulasi multisensorik, gangguan berbahasa, specific language impairment